2022
DOI: 10.3390/biomedicines10020316
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Options for Systemic Sclerosis: Current and Future Perspectives in Tackling Immune-Mediated Fibrosis

Abstract: Systemic sclerosis (SSc) is a severe auto-immune, rheumatic disease, characterized by excessive fibrosis of the skin and visceral organs. SSc is accompanied by high morbidity and mortality rates, and unfortunately, few disease-modifying therapies are currently available. Inflammation, vasculopathy, and fibrosis are the key hallmarks of SSc pathology. In this narrative review, we examine the relationship between inflammation and fibrosis and provide an overview of the efficacy of current and novel treatment opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 206 publications
0
5
0
Order By: Relevance
“…Previous studies have implicated M2 macrophages in IPF pathogenesis, with pro-fibrotic M2 macrophages characterized by expression of CD206 as well as increased metabolism of arginine into ornithine and urea by arginase ( Ruaro et al, 2019 ; Papadimitriou et al, 2022 ). Stimulation of macrophages with profibrotic cytokines IL-4 and IL-13 lead to an increased number of M2 macrophages and fewer M1 macrophages indicative of a pro-fibrotic polarization.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have implicated M2 macrophages in IPF pathogenesis, with pro-fibrotic M2 macrophages characterized by expression of CD206 as well as increased metabolism of arginine into ornithine and urea by arginase ( Ruaro et al, 2019 ; Papadimitriou et al, 2022 ). Stimulation of macrophages with profibrotic cytokines IL-4 and IL-13 lead to an increased number of M2 macrophages and fewer M1 macrophages indicative of a pro-fibrotic polarization.…”
Section: Resultsmentioning
confidence: 99%
“…Papadimitriou et al. summarized the link between the innate and adaptive arms of the immune system in the pathological mechanisms of SSc in the context of the currently available treatment regimen ( 16 ). Nagafuchi et al.…”
Section: Introductionmentioning
confidence: 99%
“…This is exemplified by the development of a dysregulated Raynaud’s phenomenon as the first and principal disease manifestation. T lymphocytes have been detected in SSc-affected tissues and multiple studies have suggested their potential involvement in the observed fibrosis and vasculopathy through the production of cytokines such as interleukin (IL)-4, IL-13 and IL-17 3. Unexpectedly, a recent study showed a prominent role for cytotoxic T cells in mediating SSc skin pathology 4.…”
Section: Introductionmentioning
confidence: 99%